Caution on determining divide migration from cross‐divide contrast in χ. Issue 10 (26th June 2022) - Wu, Yunpeng; Yang, Rong; He, Chuanqi; He, Junqing
Abstract : The landscapes on Earth are shaped by the interaction of tectonics and erosion processes and thus is a recorder for past tectonic and climatic histories. A recently proposed geomorphologic index for fluvial landscape, χ, can indicate the drainage divide migration from the smaller‐ χ ‐value side to the other and provide a quick estimation of the dynamic state of drainage systems. Since then, this index has been frequently used to determine divide mobility and hence landscape evolution. Some factors, however, have substantial impacts on the interpretation of the χ value, including tectonic activities, rock erodibility, and precipitation differences. Here we set a series of numerical simulations implemented on the landscape evolution model of DAC (Divide and Capture). Each simulation includes a spatial variation of a particular factor to examine the relationship between divide migration and χ values. Our numerical modelling results indicate that the migration direction is related to cross‐divide contrast in erosion rate rather than χ . We take the Wula Shan horst as a natural example to demonstrate a static drainage divide but with discrepancies of cross‐divide χ values in a setting of spatially asymmetric uplift. Our results suggest that a straightforward relationship between cross‐divide contrasts in χ values and the drainage divide motion may not exist when spatial and temporal variations exist in the rock uplift rate, lithology, and precipitation. We emphasize that researchers should take notice of the requisite assumptions and scope of the application when using this index in landscape analysis. Abstract : Numerical simulations and a natural example suggest the decoupling of divide mobility and cross‐divide χ value in the area with complex geological settings. We emphasize that researchers should take notice of the premise and scope of application when using χ in landscape analysis.